Organic iron and iodine in laying hen diet: Performance, egg quality, thyroid hormones, antioxidant status, serum and yolk lipids, and egg iron and iodine contents - Sima Sarlak; Sayed Ali Tabeidian; Majid Toghyani; Amir Davar Foroozandeh Shahraki; Mohammad Goli; Mahmood Habibian (Journal of Trace Elements and Minerals)
Introduction: Eggs can be enriched with iron and iodine through the diet. However, high levels of iron and iodine negatively influence the egg quality and performance of birds. This problem may be overcome by organic forms of minerals. Materials and methods: In this study, the effects of ferrous glycine and ethylenediamine dihydroiodide as sources of iron and iodine on hen performance, egg quality, antioxidant status, and iron and iodine contents of eggs were evaluated in a 16-wk dietary experiment. A factorial arrangement including 3 levels (0, 120, 240 mg.kg-1) of supplemental iron and 3 levels (0, 1.0, and 5.0 mg.kg-1) of supplemental iodine was utilized. Results: Dietary iodine did not affect bird performance. However, egg laying and feed intake decreased, and feed conversion ratio increased in the absence of supplemental iron. Diets without supplemental iron increased abnormal eggs along with decreasing the eggshell quality (weight, thickness, strength, and calcium content) and disturbing the serum and egg yolk lipids. This paralleled the reduction of serum thyroxine and triiodothyronine and disruption of the oxidative status in the serum and eggs. The highest production of abnormal eggs and the lowest eggshell weight and thickness occurred with diet containing no supplemental iron and 0.5 mg.kg-1 of iodine. The application of iron and iodine resulted in elevated levels of these elements in the eggs, with the increase in iodine content demonstrating a dose-dependent relationship. Moreover, while iron contents were constant between 8 and 16 wk, iodine contents showed increasing trends with 0.5 mg.kg-1 of iodine. Conclusion: It is advisable to enhance the diet with 120 mg.kg-1 of organic iron and 1 mg.kg-1 of organic iodine to ensure optimal performance, egg quality, and overall health in laying hens.